ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DISMENOREA PADA SANTRI PUTRI DI PONDOK PESANTREN HAFSHAWATY - Dhika Siti Mona; Achmad Kusyairi; Ainul Yaqin Salam (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Dysmenorrhea is an discomfort during menstruation during the most frequent first or second days. The saboteur factor, the age of writing, the habit of eating fast food, and turning down coffee. The purpose of research is to find out what factors related to the incidence of dysmenorea on the women's orderlies in hafshawaty's log cabin Research design uses Correlational analytic with a sectional cross approach. The population of 320 respondents and samples uses a simple random sampling technique of 283. The instrument used questionnaire. Further analysis using the sperman and regression ordinal test.The results of this study show that fast food consumption in the moderate category was found in 195 respondents (68.9%), high-level coffee consumption in 158 respondents (55.8%), and early menarche in 207 respondents (73.1%). The dominant factor was fast food consumption, with a Wald value of 46.848. The analysis showed a significant relationship (p = 0.000 < α = 0.05) between the three factors and the incidence of dysmenorrhea.The findings suggest that the earlier the age of tower dancing, the higher the risk of dysmenorrhea. This can be explained physiologists because early dancing is mainly linked to estrogen and progesterone imbalance that triggers the contraction of the uterus more strongly. Additionally, fast food and coffee consumption contributes to increased prostaglandin levels that worsen menstrual pain. Is important advisors in precenting and handing dysmenorrhea.